BAHASA SEBAGAI HAMBATAN DAN JEMBATAN: TANTANGAN KOMUNIKASI PERDAGANGAN DI DAERAH BERBEDA - Zikra Andini Mardhiyah; Rahmi Armanda Putri; Perawati (Journals of Indonesian Multidisciplinary Research, 2025)
Indonesia's linguistic diversity presents a distinct challenge in fostering interregional business communication. Language may serve as a barrier when business actors come from different cultural and linguistic backgrounds, but it can also become a bridge that strengthens trade relationships when used strategically. This article is a literature review that explores the dual role of language in the context of local trade through the analysis of several scholarly sources. The findings indicate that proficiency in the Indonesian language, contextual use of local terms, and the support of communication technology play significant roles in overcoming language barriers. The study recommends enhancing intercultural communication strategies and optimizing digital technology as relevant solutions for trade interaction across regions.